Genesis, n° 41, «Créer à plusieurs mains» (Prassi Ecdotiche della Modernità Letteraria, 2016)
Genesis (Manuscrits - Recherche - Invention) is a biannual French periodical promoted by the Institut des textes et manuscrits modernes (ITEM) of Paris, the center of researches on genetic criticism, which has many team working on the main authors of French and European Literature of the XVIIth Century (Rousseau, Voltaire), of the XIXth century (Flaubert, Zola), of XXth century (Proust, Joyce, and also Aragon, Barthes, Celan, Valéry), of Philosophy (Nietzsche, Sartre). Genesis was founded in 1992 and is now edited by PUPS. Presses de l'Université Paris-Sorbonne, under the direction of Daniel Ferrer and Almuth Grésillon.The periodical has many sections: Enjeux (papers on a selected theme); Études (with studies on genetic criticism); Entretien (where authors talk about how they work); Inédit (where are published unpublished works); Archives (with studies on archive collections and some suggestion on future researches); Varia (papers); Chroniques (informations and thought on events, conventions, books about genetic criticism. Two years after the prints, issues are available on the periodical’s website: http://genesis.revues.org/This is the last issue of Genesis, 41/2015, focused on hand-in-hand writing process (Créer à plusieurs mains), edited by Nicolas Donin and Daniel Ferrer.
Keywords: Collaborative creation; authorship; author; author’s revision; variants; genetic criticism; critique genetique; genetic dossier